Modern Teacher Profile: A Conceptual Analysis of Competencies, Challenges, and Development Strategies in 21st Century Education - Vin Rafin (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The educational transformation of the 21st century has shifted the role of teachers from mere transmitters of knowledge to facilitators of learning, character mentors, learning leaders, and agents of change. This shift demands a comprehensive conceptual understanding of the profile of modern teachers. Objective: This study aims to analyze the profile of modern teachers from an educational perspective by synthesizing the scientific literature. Method: This study used a qualitative approach, applying Qualitative Content Analysis to relevant scientific articles, books, regulations, and academic documents. The analysis was conducted through a process of coding, categorization, and thematic synthesis. Results: The study identified four major themes: the conceptual reconstruction of the teacher role, teacher characteristics and competencies, 21st-century educational challenges, and professional development strategies. The findings show that the profile of modern teachers is shaped by the integration of pedagogical, professional, social, personal, and leadership competencies, as well as 21st-century skills, specifically digital literacy, communication, creativity, collaboration, and adaptability. Conclusion: Teacher professionalism requires holistic, sustainable development to effectively respond to educational dynamics and meet the demands of 21st-century learning. Contribution: This study offers a conceptual framework that integrates various dimensions of the teacher profile as a foundation for policy development, teacher competency improvement programs, and future empirical research.